LITERASI KEWIRAUSAHAAN DAN TEKNOLOGI DI DUSUN MIMBO MENUJU DESA PESISIR MANDIRI DI DUSUN MIMBO - Eni Erwantiningsih; Danu Prantas; Achmad Zulpan Abida (Indonesian Journal of Engagement, Community Services, Empowerment and Development, 2023)
Mimbo Hamlet is one of the hamlets in Jatirejo Village, Lekok District, Pasuruan Regency. As a hamlet located in a coastal area, the natural potential, especially marine products, is very abundant. The majority of people have livelihoods as fishermen and traders in the market. The location of the hamlet which is far from the main access road connecting Pasuruan Regency and other cities makes this area difficult regarding the flow of information. Technological developments and entrepreneurial literacy that are actually needed by the community are very limited. Meanwhile, the community's skills and creativity in managing local potential in Mimbo hamlet are very well developed. Fishermen's marine products so far cannot be enjoyed economically because fishermen are still dependent on middlemen who provide capital in finding fish. Fish catches are purchased at low prices and have to pay for the start-up costs of their business. It is this economic limitation that encourages fishing families, especially housewives, to be creative with the sea catches they get. The community processes unsold fish into fish crackers, fish rengginang and shrimp paste. While other villagers are also trying to make a fortune by selling Arabic coffee, herbal medicine and even other handicrafts, namely creations from shells. Shells are used as the basic material for mosaic crafts, ashtrays, flower pots and accessories. The community even processes local plant products, namely the leaves of the mimbo plant, into herbal medicine which is brewed in the form of tea. It is this limited product and technology marketing literacy that limits them from developing innovative results to a larger market. The people's desire to penetrate markets outside the region is only a dream that has no end. This condition increasingly makes the box that limits them because the location of the area is indeed far from the reach of the general public. Apart from that, no public transportation passes Mimbo Hamlet except for the local people themselves who travel. This situation certainly does not provide broad opportunities for the people of Mimbo Hamlet to progress like other regions. The fighting spirit that coastal areas also have potential cannot be known by many people. Therefore it is very important to provide insight and literacy regarding technology and marketing as well as related regulations, namely related to brands and product licensing. Insight into business financial management is also very necessary so that people can manage business finances to achieve business goals. It is hoped that this increase in insight will allow the community to be independent in developing entrepreneurial opportunities and be able to compete with outsiders. The independence of this community can also support Jatirejo village as a marine tourism village in Pasuruan Regency